Economic Secularization and its Impact on the Islamic Economic System - Karimullah, Suud Sarim (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2024)
The main objective of this study is to deepen the understanding of how Islamic values can be integrated into the modern economic system, thereby creating a more inclusive, just, and welfare-oriented economic model. This study uses library research to access and analyze various sources of information relevant to an integrative literature analysis. The results of the study confirm that economic secularization. However, it has dominated the global system with a paradigm of materialism and individualism, simultaneously opening opportunities for Islamic economics to offer transformational solutions that are more ethical, inclusive, and sustainable. By reconstructing the Sharia-based paradigm, integrating the values of justice and solidarity into modern economic practices, and strengthening Islamic economic institutions through innovation and professionalism, this system can go beyond simply being an alternative to capitalism and socialism. Islamic economics has excellent potential to create a global economic order oriented towards human welfare and make it relevant in the modern era and as a universal solution that addresses the world's pressing needs.